2020
DOI: 10.1126/scitranslmed.aay3575
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of immune checkpoints in lymph nodes through locoregional delivery augments cancer immunotherapy

Abstract: Systemic administration of immune checkpoint blockade (ICB) monoclonal antibodies (mAbs) can unleash antitumor functions of T cells but is associated with variable response rates and off-target toxicities. We hypothesized that antitumor efficacy of ICB is limited by the minimal accumulation of mAb within tissues where antitumor immunity is elicited and regulated, which include the tumor microenvironment (TME) and secondary lymphoid tissues. In contrast to systemic administration, intratumoral and intradermal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
156
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 52 publications
8
156
0
Order By: Relevance
“…We reported that peritumoral delivery of anti-CTLA-4 in mouse models resulted in an equally efficient antitumor response as observed after systemic administration, without the usually associated inflammatory side effects (65). A recent report from Francis et al (6) elegantly showed in tumor models that intratumoral administration of CTLA-4 and/or PD-1 blocking antibodies ensured optimal access to TDLN (in contrast to systemic administration) and, moreover, that ipsilateral administration on a site different from the tumor but with lymph drainage to the same lymph node stations afforded equal tumor protection. This is in line with our own observations of the induction of systemic and protective antimelanoma immunity in early-stage melanoma through local immune modulation of the SLN after surgical removal of the primary tumor, either by CpG-B (44) or by anti-CTLA-4 (71).…”
Section: In Conclusion: the Rise Of Local Immunotherapymentioning
confidence: 74%
See 2 more Smart Citations
“…We reported that peritumoral delivery of anti-CTLA-4 in mouse models resulted in an equally efficient antitumor response as observed after systemic administration, without the usually associated inflammatory side effects (65). A recent report from Francis et al (6) elegantly showed in tumor models that intratumoral administration of CTLA-4 and/or PD-1 blocking antibodies ensured optimal access to TDLN (in contrast to systemic administration) and, moreover, that ipsilateral administration on a site different from the tumor but with lymph drainage to the same lymph node stations afforded equal tumor protection. This is in line with our own observations of the induction of systemic and protective antimelanoma immunity in early-stage melanoma through local immune modulation of the SLN after surgical removal of the primary tumor, either by CpG-B (44) or by anti-CTLA-4 (71).…”
Section: In Conclusion: the Rise Of Local Immunotherapymentioning
confidence: 74%
“…Such earlyeffector or progenitor-exhausted T cells can persist for long times in the TDLN in the absence of antigen, are polyfunctional, display a high proliferative capacity and share phenotypic traits with central-memory T cells (58). Upon PD-1 blockade they can efficiently home to the TME and there expand further and differentiate into effector T cells (6,26). In keeping with this, Chow et al showed that expression of CXCR3, required for tumor rejection after PD-1 blockade in the MC38 mouse model, was expressed at high levels by progenitor-exhausted or early-effector T cells, whereas it was hardly expressed by terminally exhausted T cells (59).…”
Section: Overcoming Immune Exclusion By Targeting DC In Tdln: Reinvigmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating results were reported by recent clinical trials involving cancer immunotherapy with various immune checkpoint inhibitors (ICIs)—including antibodies against cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and monoclonal antibodies (mAbs) against both programmed cell death-1 and the dysfunction/activation of cytotoxic T lymphocytes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The blockade of immune checkpoints by ICIs reinvigorates dysfunctional T cells by restoring tumor-specific immunity for the eradication of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies will be needed to test what signals are necessary for maintenance and migration of T cells in dLNs.The role of the dLN in immunotherapy remains uncertain. Expression of PD-L1on DCs is important for responses to anti-PD-L1 in some tumor models, and migratory DCs in tumor dLNs express both PD-L1 and the costimulatory receptor B7-2 (98).Moreover, PD-1 blockade can act in dLNs in transplant tumor models(99,100).Whether PD-1 blockade acts outside the TME in humans is not known, but therapeutic efficacy after anti-PD-1 treatment in patients is associated with changes in immune cell populations in the peripheral blood(101,102) and with the appearance of new T cell clones in the tumor after therapy(103)(104)(105). Our analyses of CD8 T cells from humans showed the presence of TSL-like cells in LNs and tumors.…”
mentioning
confidence: 99%